China’s Belt and Road Initiative as a Strategy for Hegemonic Contestation in the Indo-Pacific Region - Martua Sitompul (TALENTA Publisher, Universitas Sumatera Utara, 2025)
This article examines China's Belt and Road Initiative (BRI) as a strategicinstrument in its efforts to challenge the existing hegemonic order in the IndoPacific region. Amid growing geopolitical rivalry, particularly with the UnitedStates and its allies, China has employed the BRI not merely as an economicdevelopment scheme, but as a tool of influence projection, regional integration,and soft power consolidation. Using a qualitative-descriptive approach andcritical geopolitical analysis, this study explores how China’s BRI projects ranging from infrastructure development to digital connectivity are reshapingregional power dynamics. The research finds that China’s approach blendseconomic diplomacy with strategic interest, fostering dependencies andinfluence in key Indo-Pacific states. However, the implementation of BRI alsoencounters resistance in the form of debt-trap diplomacy allegations,environmental critiques, and counter-initiatives like the U.S.-led Indo-PacificStrategy. The article concludes that the BRI is central to China’s vision of aSinocentric order, signaling a shift from unipolar to multipolar geopoliticalcompetition in the Indo-Pacific.